PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN (STUDI KASUS PADA HOTEL RATU MAYANG GARDEN PEKANBARU) - Angga Kusuma; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the effect of Transformational Leadership Style and Working Environment on Employee Satisfaction (Case Study at Hotel Ratu Mayang Garden Pekanbaru). Transformational Leadership Style as a variable ( X1 ) Working Environment as a variable ( X2 ) and Job Satisfaction as ( Y ).The method in this research is descriptive and quantitative using SPSS 20. The samples used were 92 employees, consisting of 10 departments . To determine the sample using census study . Data collection through questionnaires .Results of analysis using multiple linear regression , t test , and test f . It can be seen that the Transformational Leadership Style variables significantly influence Job Satisfaction , Work Environment significant effect on Job Satisfaction , and Transformational Leadership Style and Working Environment significant effect on Employee SatisfactionKeywords : Transformasional Leadership Style, Work Environment, and Employee Satisfaction